Collaborative Ecosystems and Performance Constraints of Islamic MSMEs: Evidence from Magelang Raya - Wahyudi, Muhamad; Iswanaji, Chaidir; Khotijah, Siti Afidatul; Panggiarti, Endang Kartini; Wicaksono, Alfin Rochman (Institut Bisnis dan Informatika Kesatuan, 2025)
Islamic MSMEs have become an important driver of Indonesia’s growing Islamic economic sector, yet their development is still constrained by limited financing access, weak managerial capacity, and insufficient ecosystem support. Despite strong potential across various regions, the lack of comprehensive data and persistent structural barriers continue to hinder efforts to strengthen their competitiveness and long-term sustainability. This study aims to analyze the potential, challenges, and strengthening strategies of Islamic MSMEs in Magelang Raya. A mixed-method approach was employed, combining survey data from 214 respondents with focus group discussions involving stakeholders. The findings reveal that Islamic MSMEs possess great potential with a relatively high level of sharia compliance but face major obstacles such as limited access to Islamic financing, low financial literacy, and weak institutional support. Cross-tabulation analysis shows significant relationships between the number of employees and the need for external support, while Exploratory Factor Analysis identifies latent factors including limited capital, mentoring, and market access. Strengthening strategies based on Maqashid Sharia, Resource-Based View, and the Entrepreneurial Ecosystem framework recommend multi-stakeholder collaboration in providing sharia financing, managerial training, and digital marketing to enhance the competitiveness of Islamic MSMEs in Magelang Raya.